2017
DOI: 10.1038/541455a
|View full text |Cite|
|
Sign up to set email alerts
|

Journals invite too few women to referee

Abstract: Journals invite too few women to refereeJory Lerback and Brooks Hanson present an analysis that reveals evidence of gender bias in peer review for scholarly publications. US geoscientists on an expedition in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
222
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(243 citation statements)
references
References 9 publications
10
222
0
4
Order By: Relevance
“…In this study, we found that apart from a few outliers depending on country and discipline, women are underrepresented in the scientific community with a very slow trend towards balance, which is consistent with earlier studies (Larivière et al, 2013; Fox et al, 2016; Topaz and Sen, 2016; Lerback and Hanson, 2017; Nature Neuroscience, 2006; Shen, 2013; Nature, 2012). In addition, we found that women contribute to the system-relevant peer-reviewing chain even less than expected by their numerical underrepresentation, revealing novel and subtler forms of bias than numeric disproportion alone.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that apart from a few outliers depending on country and discipline, women are underrepresented in the scientific community with a very slow trend towards balance, which is consistent with earlier studies (Larivière et al, 2013; Fox et al, 2016; Topaz and Sen, 2016; Lerback and Hanson, 2017; Nature Neuroscience, 2006; Shen, 2013; Nature, 2012). In addition, we found that women contribute to the system-relevant peer-reviewing chain even less than expected by their numerical underrepresentation, revealing novel and subtler forms of bias than numeric disproportion alone.…”
Section: Discussionsupporting
confidence: 91%
“…In the geosciences, for example, although there are significant numbers of women earning geoscience degrees in the US ) these numbers are not translating into equivalent female representation in academic faculty (Glass 2015) or professional activities such as journal refereeing (Lerback and Hanson 2017). Similarly, lower than expected representation of women has been observed in editorial boards in mathematics (Topaz and Sen 2016) and as invited conference speakers in ecology and conservation (Schroeder et al 2013;Sardelis and Drew 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Although there are many reasons for this “leaky pipeline” (Gasser & Shaffer, 2014; Goulden, Mason, & Frasch, 2011; Holmes, OConnell, & Dutt, 2015), increasing training and avoiding biases in reference letters may benefit not only women, but also the greater scientific community by promoting innovation through diversity and inclusion. Further, there are many topics such as referee opportunity bias (Lerback & Hanson, 2017), the childcare‐conference conundrum (Calisi & A Working Group of Mothers in Science, 2018), and misconceptions around hiring preferences (Williams & Ceci, 2015) that should also be addressed to reduce disadvantages to women. With the brief mention of this topic, we hope to stimulate future studies of gatekeeping practices in the field of conservation, so institutions can develop initiatives to recruit, retain, and advance women in STEM fields as mentorship will be essential for eliminating gender bias in computer science, bioinformatics, and by extension, conservation biology.…”
Section: Increasing Contributions By Women (Sarah Hendricks and Brennmentioning
confidence: 99%